The Effect of Village Funds, Village Fund Allocations, Tax, and Levy Revenue Sharing Funds on Poverty in Banjarnegara Regency - Nugroho Ari Putra; Lilis Siti Badriah; Suharno Suharno; Chandra Suparno (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2023)
Poverty is a problem that exists in every country including Indonesia. Government policies in an effort to alleviate poverty are carried out by disbursing Village Funds, Village Fund Allocations and Tax and Levy Revenue Sharing. Village Fund is a fund sourced from the State Budget that is transferred through the Regency/City Budget and is used to finance the implementation of Village authority based on the right of origin, and village-scale local authority. The Village Fund Allocation is part of the village finance obtained from the Regional Tax Revenue Sharing and part of the Central and Regional Financial Balance Fund received by the district which is then transferred to the village to support the implementation of the village government. Meanwhile, the Tax and Levy Revenue Sharing is a budget received by the village as part of the tax and levy proceeds from the regency/city area at least 10% of the realization of tax and levy revenues. This study discusses the effect of village funds, village fund allocation and tax and levy revenue sharing on poverty in Banjarnegara Regency. Panel data regression with the fixed effect model method is the methodology used in this study. The regression results showed that the variables of village funds and tax and levy revenue sharing had a negative and significant effect on reducing poverty in Banjarnegara Regency. Meanwhile, the variable allocation of village funds has a positive effect on reducing poverty in Banjarnegara Regency.Keywords: Village Fund, Village Fund Allocation, Tax and Levy Revenue Sharing, Poverty